High oscillator strength interlayer excitons in two-dimensional heterostructures for mid-infrared photodetection - Lukman, Steven (2020)
The development of infrared photodetectors is mainly limited by the choice of available materials and the intricate crystal growth process. Moreover, thermally activated carriers in traditional III-V and II-VI semiconductors enforce low operating temperatures in the infrared photodetectors. Here we demonstrate infrared photodetection enabled by interlayer excitons (ILEs) generated between tungsten and hafnium disulfide, WS2/HfS2. The photodetector operates at room temperature and shows an even higher performance at higher temperatures owing to the large exciton binding energy and phonon-assisted optical transition. The unique band alignment in the WS2/HfS2 heterostructure allows interlayer bandgap tuning from the mid- to long-wave infrared spectrum. We postulate that the sizeable charge delocalization and ILE accumulation at the interface result in a greatly enhanced oscillator strength of the ILEs and a high responsivity of the photodetector. The sensitivity of ILEs to the thickness of two-dimensional materials and the external field provides an excellent platform to realize robust tunable room temperature infrared photodetectors.